Eradication of infection, survival, and radiological results of uncemented revision stems in infected total hip arthroplasties: 28 one-stage and 53 two-stage exchanges with a mean follow-up of 7 years. (1st November 2016) - Born, Philipp; Ilchmann, Thomas; Zimmerli, Werner; Zwicky, Lukas; Graber, Peter; Ochsner, Peter E; Clauss, Martin
Abstract : Background and purpose — The use of uncemented revision stems is an established option in 2-stage procedures in patients with periprosthetic joint infection (PJI) after total hip arthroplasty (THA). However, in 1-stage procedures, they are still rarely used. There are still no detailed data on radiological outcome after uncemented 1-stage revisions. We assessed (1) the clinical outcome, including reoperation due to persistent infection and any other reoperation, and (2) the radiological outcome after 1- and 2-stage revision, using an uncemented stem. Patients and methods — Between January 1993 and December 2012, an uncemented revision stem was used in 81 THAs revised for PJI. Patients were treated with 1- or 2-stage procedures according to a well-defined algorithm (1-stage: n = 28; 2-stage: n = 53). All hips had a clinical and radiological follow-up. Outcome parameters were eradication of infection, re-revision of the stem, and radiological changes. Survival was calculated using Kaplan-Meier analysis. Radiographs were analyzed for bone restoration and signs of loosening. The mean clinical follow-up time was 7 (2–15) years. Results — The 7-year infection-free survival was 96% (95% CI: 92–100), 100% for 1-stage revision and 94% for 2-stage revision (95% CI: 87–100) (p = 0.2). The 7-year survival for aseptic loosening of the stem was 97% (95% CI: 93–100), 97% for 1-stage revision (95% CI: 90–100) and 97% for 2-stage revision (95% CI: 92–100) (p = 0.3). No further infection or aseptic loosening occurred later than 7 years postoperatively. The radiographic results were similar for 1- and 2-stage procedures. Interpretation — Surgical management of PJI with stratification to 1- or 2-stage exchange according to a well-defined algorithm combined with antibiotic treatment allows the safe use of uncemented revision stems. Eradication of infection can be achieved in most cases, and medium- and long-term results appear to be comparable to those for revisions for aseptic loosening.